Neonatal blood lead concentration predicts medium term lead-related outcomes in children ≤5 years old with congenital lead poisoning: A retrospective cohort study in Northern Nigeria. - Natalie Thurtle; Katharine A Kirby; Jane Greig; Karla Bil; Paul I Dargan; Godwin N Ntadom; Nicholas A Buckley (Public Library of Science (PLoS), 2023)
Mother-to-child-transmission of lead via the placenta is known to result in congenital lead toxicity. Between 2010 and 2021, Médecins Sans Frontières and other stakeholders responded to a severe lead poisoning outbreak related to artisanal gold mining in Northern Nigeria. Extensive environmental remediation occurred following outbreak identification; source control efforts are ongoing within the community. We aimed to describe the prevalence of congenital lead poisoning in this cohort and analyse the association between neonatal blood lead concentration (BLC) and medium-term lead-related outcomes during the study period. Children enrolled in the lead poisoning programme between July 2010 and 25 January 2018 who had a screening BLC at ≤4 weeks of age were included. For time-to-event analysis, medium-term outcomes were classified as lead-related (death from lead encephalopathy, and/or met chelation threshold) and non-lead-related (non-lead-related death, on programme no chelation, exit from programme without chelation). Cox regression analysis and ROC analysis were performed. 1468 children were included. All-cause mortality 2.3%; geometric mean neonatal BLC 13.7 μg/dL; 'lead-related death or treatment' 19.3%. For every doubling in neonatal BLC, there was an almost 8-fold increase in adjusted hazard ratio (HR) for the composite lead-related outcome (p<0.001). A neonatal BLC ≥ 15.0 μg/dL had 95% sensitivity for identifying children who went on to have the composite outcome (with specificity 67%; positive likelihood ratio 2.86). Congenital lead poisoning predicts ongoing exposure in this population, even after environmental remediation. This suggests a complex, early, multidisciplinary approach to source control and exposure management is required when elevated neonatal BLC is observed in lead poisoning clusters in low-and-middle-income contexts.